2020
DOI: 10.1093/icesjms/fsaa086
|View full text |Cite
|
Sign up to set email alerts
|

Ocean acidification induces carry-over effects on the larval settlement of the New Zealand abalone,Haliotis iris

Abstract: Larval settlement is a key process in the lifecycle of benthic marine organisms; however, little is known on how it could change in reduced seawater pH and carbonate saturation states under future ocean acidification (OA). This is important, as settlement ensures species occur in optimal environments and, for commercially important species such as abalone, reduced settlement could decrease future population success. We investigated how OA could affect settlement success in the New Zealand abalone Haliotis iris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…Our results also showed that pH decrease did not have any impact on post-larval settlement 9 days after fertilisation. These results are consistent with previous findings in H. tuberculata (Kavousi et al, 2021) and H. kamtschatkana (Crim et al, 2011) Velasco et al, 2021;Tahil and Dy, 2016). These contrasting effects among Haliotis species may be due either to differences in larval sensitivity or to other indirect effects of decreased pH on the settlement substrate, as previously shown in abalone larvae (O'Leary et al, 2017).…”
Section: Post-larval and Juvenile Evaluationsupporting
confidence: 93%
“…Our results also showed that pH decrease did not have any impact on post-larval settlement 9 days after fertilisation. These results are consistent with previous findings in H. tuberculata (Kavousi et al, 2021) and H. kamtschatkana (Crim et al, 2011) Velasco et al, 2021;Tahil and Dy, 2016). These contrasting effects among Haliotis species may be due either to differences in larval sensitivity or to other indirect effects of decreased pH on the settlement substrate, as previously shown in abalone larvae (O'Leary et al, 2017).…”
Section: Post-larval and Juvenile Evaluationsupporting
confidence: 93%
“…Thus, the timing and magnitude of environmental change is likely to have a joint effect on plasticity (Donelson et al, 2018). Carryover effects of environmental history have physiological (Espinel‐Velasco et al, 2021; Parker et al, 2012), ecological (Costantini, 2014; Hettinger et al, 2013) and evolutionary implications (Thomsen et al, 2017). In light of this, it is essential to understand how intermittent or repeated environmental signals, such as the challenges posed from climate change, are transduced to elicit acclimatory mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…On an industrial scale, the most striking illustration of possible OA effects is the correlation between the pH of seawater and the survival of oyster larvae, clearly linking the pH T / pCO 2 of seawater to hatchery failures (Barton et al, 2012). Espinel-Velasco et al (2021) investigated how OA influenced settlement success in the New Zealand abalone, Haliotis iris. They examined direct effects of seawater pH T at the time of settlement, indirect effects of pH on settlement substrates made of crustose coralline algae (a calcifying organism susceptible to OA) and carryover effects by examining settlement in larvae reared to competency at ambient and reduced pH.…”
Section: An Overview Of the Contributions In This Article Theme Setmentioning
confidence: 99%
“…Indeed, these approaches are essential for understanding the effects of climate change and providing guidelines to policymakers (Riebesell and Gattuso, 2015). The research articles that we received were generally multi-factorial (Endo et al, 2021;Espinel-Velasco et al, 2021;Godwin et al, 2021;Nordio et al, 2021;Shephard and Gargan, 2021) and several address adaptation issues (Clements et al, 2021;Espinel-Velasco et al, 2021;Nordio et al, 2021). However, they focus on the species of interest and pay relatively little attention to other ecosystem components.…”
Section: Summary and Forward Lookmentioning
confidence: 99%